2014
DOI: 10.1002/eco.1457
|View full text |Cite
|
Sign up to set email alerts
|

Modelling soil moisture, water partitioning, and plant water stress under irrigated conditions in desert urban areas

Abstract: This study conducts a comparative analysis of the effects of irrigation scheduling at two urban residential sites in the Phoenix, Arizona, metropolitan area: a xeriscaped site (gravel base with low water use plants) and a mesiscaped site (turf grass and shade trees). A model of soil moisture dynamics was calibrated to observed soil moisture data from irrigated and non‐irrigated sensors at the xeric site and an irrigated sensor at the mesic site. Model simulations were conducted at both irrigated sites to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 37 publications
2
44
0
Order By: Relevance
“…Because of the soil compaction, water shortage, especially in interaction with other environmental drivers, can be also an important factor in urban environments. A number of studies have recently focused on plant water use and thresholds of water stress [20,21]. It has been further demonstrated that higher temperature and increased drought in urban environments significantly affected the growth of urban trees [2,22].…”
Section: Studying Vegetation Along the Urban-rural Gradientmentioning
confidence: 99%
“…Because of the soil compaction, water shortage, especially in interaction with other environmental drivers, can be also an important factor in urban environments. A number of studies have recently focused on plant water use and thresholds of water stress [20,21]. It has been further demonstrated that higher temperature and increased drought in urban environments significantly affected the growth of urban trees [2,22].…”
Section: Studying Vegetation Along the Urban-rural Gradientmentioning
confidence: 99%
“…As shown in Figure 4, precipitation is partitioned into rainfall, snowfall, or a mixture based on T a . See text for details during the field experiment (e.g., Volo et al, 2014). We added snowmelt S m to total water input X (mm day −1 ) to the biocrust layer, if present.…”
Section: Biological Soil Crust Ecohydrology Modelmentioning
confidence: 99%
“…One-dimensional soil water balance models have been shown to capture essential interactions between climate, soil, and vegetation under natural and irrigated conditions in drylands (e.g., Volo, Vivoni, Martin, Earl, & Ruddell, 2014). One-dimensional soil water balance models have been shown to capture essential interactions between climate, soil, and vegetation under natural and irrigated conditions in drylands (e.g., Volo, Vivoni, Martin, Earl, & Ruddell, 2014).…”
mentioning
confidence: 99%
“…Miller et al, (2007) calibrated soil moisture pdfs to project vegetation stress in a changing climate. Chen et al, (2008) related evapotranspiration observations at the stand scale to soil moisture values using a Bayesian inversion approach, and Volo et al, (2014) calibrated the soil moisture loss curve to investigate effects of irrigation scheduling and precipitation on soil moisture dynamics and plant stress. The functional form of the soil moisture losses was 25 approximated using conditionally averaged precipitation (Salvucci, 2001;Saleem and Salvucci, 2002) and remotely sensed data (Tuttle and Salvucci, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Soil saturation pdfs are less sensitive to the many sources of uncertainty and common gaps in soil moisture observations and do not require high quality co-located and concurrent hydrologic measurements that are often lacking. A number of studies have combined inverse modeling 10 approaches with ground and remotely sensed soil moisture data to successfully extract meaningful hydrologic information (Xu et al, 2006;Miller et al, 2007;Chen et al, 2008;Volo et al, 2014;Wang et al, 2016;Baldwin et al, 2017). In particular, Bayesian inference methods are effective in relating prior pdfs of observations to posterior estimates of model parameters (Xu et al, 2006;Chen et al, 2008;Baldwin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%